A Breakthrough in Cardiology: Machine Learning's Power in Unmasking Long QT Syndrome - Akhtar, Syed Owais; Venkata, Hemanth Kesani; Mujaddadi, Khunsha; Kamal, Anosha Aslam; Singh, Taranpreet; Anum, Natasha; Khalid, Saif; Ansari, Fazeela; Zada, Salih; Bedros, Adees Wirtan Sarkees (Cardiology and Cardiovascular Medicine, 2024)
Abstract not available in the source database.